The Mirror in La Rambla paralela [My Parallel Deaths] (2002) by Fernando Vallejo - Domínguez Torres, Mario Alberto (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The novels of the Colombian author Fernando Vallejo (1942) are auto-fictional proposals written in the first person and from a place of exile. Within them, La Rambla paralela (2002) stands out for being a novel in which the traditional first person narrator of Vallejo, creates a biographer who writes, from the third person, about the trip to Barcelona and the death of the narrator. The aim of this article is to eva - luate how the unfolding of the narrator-author in the figure of the biographer allows the first to make the novel into a mirror through which he evaluates his stylistic attributes